A framework study of school facilities performance in public primary school of Batubara district in Indonesia - Amilia, Hasbullah; Wan Zahari, Wan Yusoff; Maziah, Ismail; Vitasari, Prima (Elsevier, 2011)
School facilities have the important role to ensure the quality of teaching and learning with respect to achieve quality of education. The performance of school facilities significantly affected on student achievement. Therefore, the study on measuring school facility performance is basically important to be taken in order to provide appropriate teaching and learning environment. This paper aims to discuss about framework on measuring the performance of school facilities in public primary school in Batubara district in Indonesia. The concept of facility conditions that identified by Schneider is applied as a basis to measure school facilities performance. The proposed framework is structured through distributed questionnaire spread over Batubara district in order to find the level of school facilities performance from stakeholder perspective, in this case for those who work in school that using facilities. The level of school performance will be ranged from poor to excellent. The results are expected to be used as a guide for school to improve school facilities in public primary school in Indonesia concurrently leading to the improvement of the quality of education in Indonesia in the future.